Attribution of extreme precipitation related to a fatal derailment near Carmont, Scotland - Simon F B Tett; Christopher Long; Simon J Brown (Environmental Research: Climate)
A derailment on 2020-08-12 near Carmont, Scotland resulted in the death of three people and the injury of the other 6 people on the train. The cause of the derailment was gravel washed onto the tracks due to heavy rain and an improperly built drain. The heavy rainfall near the derailment site lasted about 4 h, with a large burst of rain just prior to the derailment. The rainfall event was heavy with return periods between 1-in-20 and 1-in-40 summers. Simple theory suggests that extreme precipitation should increase with changes in saturated humidity (Clausius–Clapeyron; CC). The UK’s convective permitting model suggests, that extreme hourly rainfall near Carmont changes at about 1.5× CC rates while extreme four hourly rates increases below CC rates. This leads to an increased probability, relative to late 19th century conditions, of hourly (4 h) extremes similar to that which occurred near the derailment by about 20 (15)% with a further frequency increase of about 20 (15)% for such events in a +2C warmer world. Some characteristics of the simulated extreme rain evaluate well against radar values, but the simulated rainfall is about 20%–30% larger than the radar rainfall. This likely reflects shortcomings in radar calibration of extreme rainfall though poor model performance is also possible.